2018
DOI: 10.1088/1367-2630/aae02d
|View full text |Cite
|
Sign up to set email alerts
|

Stability of degenerate vortex states and multi-quanta confinement effects in a nanostructured superconductor with Kagome lattice of elongated antidots

Abstract: In the present work, we directly visualize the multi-quanta cages (MQCs) consisting of the giant vortices pinned by the elongated antidots using low-temperature scanning Hall probe microscopy. The periodic but sufficiently isolated MQCs, observed at various magnetic fields, are in a good agreement with the simulated vortex states based on the time-dependent Ginzburg-Landau (tdGL) equations. Due to the competition between the interstitial vortices and the pinned giant vortices, the formation and collapse of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…These interstitial particles could potentially modify the ice rule for the particles that are sitting in the trap sites. One study has already provided evidence that the interstitial particles can actually enhance the ordering of the ice state (Xue et al, 2018). It would also be interesting to explore the dynamics of interstitial particles for different ice substrate configurations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These interstitial particles could potentially modify the ice rule for the particles that are sitting in the trap sites. One study has already provided evidence that the interstitial particles can actually enhance the ordering of the ice state (Xue et al, 2018). It would also be interesting to explore the dynamics of interstitial particles for different ice substrate configurations.…”
Section: Discussionmentioning
confidence: 99%
“…For vortices in a kagomé pinning arrangement, various ordered and disordered arrangements have been observed in imaging experiments, and it has been argued that the long-range vortex-vortex interactions are insufficient to lift the degeneracy of the different vortex configurations in the strong pinning sites (Xue et al, 2017). As the magnetic field is increased, additional vortices become trapped in the interstitial regions surrounding the pinned vortices, which could be a step toward the realization of a stuffed artificial spin ice (Xue et al, 2018). Imaging experiments for vortex configurations on the kagomé ice (Wang et al, 2018) showed the predicted kagomé ice rule obeying states (Libál et al, 2009) both at H/H 1 = 1/2, as expected, and also at the higher field of H/H 1 = 3/2, where the additional vortices occupy the interstitial regions between pinning sites.…”
Section: Annealing Proceduresmentioning
confidence: 99%
“…In addition to the vortex statics, the TDGL equations can also be used to study slowly vortex configurations [53]. In the past decades, TDGL simulations have been used to reproduce and reveal numerous experimental results [54][55][56][57][58][59][60][61]. Therefore, TDGL equations provide an elegant and powerful tool to investigate the vortex statics and dynamics as well as the critical current density, which is far simpler than any microscopic theories.…”
Section: Theoretical Formalism For Vortex Pinning By Gbsmentioning
confidence: 99%
“…Lithographic nanofabrication techniques by the complete or partial removal of the superconductor provide vortex and/ or flux trapping in small and controlled locations [13][14][15][16][17][18][19][20][21][22], which allows more regulated and, possibly, complementary vortex manipulation and guidance. The so-named antidots (ADs) provide areas of reduced, or zero, superconducting potential and may be specifically designed to match vortex lattices, further increasing the energy required to move the vortices.…”
Section: Introductionmentioning
confidence: 99%